Students’ Civic Consciousness in the Framework of Socially Oriented Project-Based Learning - M. V. Pevnaya; L. N. Boronina; E. I. Pochatkova (Высшее образование в России)
The development of student civic consciousness is an essential aim of upbringing and educational activities in Russian universities, where project-based learning successfully integrates these processes. The institutionalisation of the “Service Learning” programme in higher education actualises the search for methodological foundations and methodical solutions to assess the social effectiveness and efficiency of the implementation of this approach in the logic of project-based learning, considering the particularities of the Russian context. The article presents the findings of a semiformalised survey of experts representing 52 higher education institutions across Russia, located in 32 cities across all federal districts of the Russian Federation (purposive sampling, N-65; 2024). The study provides evidence that the engagement of Russian university students in social projects conducted within the framework of project-based learning has an impact on the process of their civic consciousness formation. The evaluation of the influence of students' participation in social projects on their civic consciousness is connected to the conviction of experts that project-based learning cultivates the professionalism and agency of students. The extent to which students engage with socially oriented project activities is dependent less on the institutional context of project-based learning in higher education institutions and more on the interest and professionalism of the staff involved in the organisation and implementation of student projects. The effectiveness of project-based learning in developing students' citizenship is higher in universities participating in the pilot “Service Learning” programme. It has been proven that the implementation of this approach in project-based learning activates the interaction of external customers with students, thus bringing higher education and practical sphere closer together.